2019
DOI: 10.1101/2019.12.26.888602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Game Theory Applications in Host-Microbe Interactions:Mycobacterium tuberculosisinfection as an example

Abstract: The game theory describes the interactions between two players and the pay-off from wining, losing or compromising. Mycobacterium tuberculosis (Mtb)-host interactions were used as an example for the application of the game theory to describe and predict the possibilities of victory for any players. The gene expression for eight main markers of host response and three Mtb virulence factors were assessed in broncho-alveolar lavage of TB + and TB  patients. The game theory showed that a variety of paths exist th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…In our previous M.tb-host study in TB-positive and TB-negative patients, the gene expression assessments showed that the main virulence factor of M.tb was Ag85B and the complex of ESAT-6-CFP-10 that M.tb uses to combat host responses. On the other hand, the effective host's response to eliminate M.tb was a Th1 cellular immune response, mainly against the predominant M.tb antigen (Ag85), implicating in the polarization of the response by the expression of transcription factor (T-bet), modulatory factors (IDO and FoxP3) and activation of effector macrophages, activating oxygen-dependent pathway, iNOS and proteolytic activities (Sharebiani et al 2020). Therefore, Ag85 was used as the most virulence factor for activation and dissemination of M.tb, while it is the most immunodominant Ag for host immune responses to produce protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous M.tb-host study in TB-positive and TB-negative patients, the gene expression assessments showed that the main virulence factor of M.tb was Ag85B and the complex of ESAT-6-CFP-10 that M.tb uses to combat host responses. On the other hand, the effective host's response to eliminate M.tb was a Th1 cellular immune response, mainly against the predominant M.tb antigen (Ag85), implicating in the polarization of the response by the expression of transcription factor (T-bet), modulatory factors (IDO and FoxP3) and activation of effector macrophages, activating oxygen-dependent pathway, iNOS and proteolytic activities (Sharebiani et al 2020). Therefore, Ag85 was used as the most virulence factor for activation and dissemination of M.tb, while it is the most immunodominant Ag for host immune responses to produce protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…They are the main cytokines in host defense against M.tb to potentiate the functions of macrophages, NK cells, and CTLs. This host response powerfully eliminates the M.tb and may establish a specific protective immunity [15] , [16] .…”
Section: Tuberculosis and The Epigenetic Alterationsmentioning
confidence: 99%
“…Most of these molecules are strong immunogenes that the host can respond to and eliminate the infection. Many other mechanisms have also been involved in the ability of M.tb to arrest phagosome maturation, DC1 forming, and Th1 differentiating [16] , but our understanding of these mechanisms remains incomplete. The host’s main immunological molecules can be considered in four different stages as the host’s strategies: (i) inflammatory reactions and leukocyte recruitment by CCRs (CCR1-7, and CXCR1,2) in response to secretion of inflammatory cytokines such as IL-1β, TNF-α, Il-6, IFN-I, IL-10, CCL-1–5, CXCL-1,-2,-3,-5,-6,-7,-8, On the other hand, the host's critical immune molecules which can play pivotal roles in the host responses toward TB manifestation, fulminant disease, latency or exacerbation including [53] .…”
Section: An Overview Of Immune Responses To Mtbmentioning
confidence: 99%
See 1 more Smart Citation
“…The model, comprised of three ordinary differential equations built by the authors of the work [24], is devoted to the the activation of the inflammatory process, where MMPs are considered within a generalized variable, which takes into account complex pro-inflammatory mediators. The game-theoretical approach to the dynamics of a medium-size network of the hostpathogen interactions determined from the gene expressions (including those, which code MMPs) in samples taken from a cohort of patients was considered in the work [25]. Additionally, a differential-equation-based model for the macrophage proinflammatory response against M. tuberculosis, including granuloma's dynamics, among the factors of which MMP-9 was considered, was constructed and analysed in work [26].…”
Section: Introductionmentioning
confidence: 99%